Empowering Batik SMEs Through Digitalization: Development of a Business Profile Website for Batik Tapak Dara - Nurchayati Nurchayati; Low Mei Peng; Vincen Brilian Adiguna; Lisa Erfi Yunita; Imelda Dea Savila (Borneo Research and Education Center, 2026)
Batik Tapak Dara is a small and medium enterprise (SME) engaged in batik craft with strong product potential, yet lacking a website as a medium for business information and promotion. This community service activity aimed to empower Batik Tapak Dara SMEs through digitalization by developing a business profile website and providing website management training to the partner. The implementation method comprised five stages: observation, needs analysis, website design and development, training, and program evaluation. The results indicate that the business profile website was successfully developed and can be utilized as a digital medium to present business information, product catalogs, and contact information. Furthermore, the training provided effectively enhanced the digital literacy of the SME owner in managing website content independently. The implementation of this website also increased business visibility and supported the digital marketing strategy of Batik Tapak Dara SMEs. These outcomes demonstrate that website development can serve as an effective strategy to support digital transformation and SME empowerment.